Ñ conseguir fazer isso
Anexos:
![](https://pt-static.z-dn.net/files/d32/3d33326669d912d76cbbcec94e14a005.jpg)
Soluções para a tarefa
Respondido por
0
Ola Eloise
a + b = 7 (I)
3c - 2d = 8 (II)
-a + 3b = 8 (III)
-2c + d = -1 (IV)
(I + II
4b = 15
b = 15/4
a = 7 - b
a = (28 - 15)/4 = 13/4
3c - 2d = 8 (II)
-4c + 2d = -2 (IV)
-c = 6
c = -6
-18 - 2d = 8
2d = -26
d = -13
S = ((a, b, c, d) (13/4, 15/4, -6, -13))
a + b = 7 (I)
3c - 2d = 8 (II)
-a + 3b = 8 (III)
-2c + d = -1 (IV)
(I + II
4b = 15
b = 15/4
a = 7 - b
a = (28 - 15)/4 = 13/4
3c - 2d = 8 (II)
-4c + 2d = -2 (IV)
-c = 6
c = -6
-18 - 2d = 8
2d = -26
d = -13
S = ((a, b, c, d) (13/4, 15/4, -6, -13))
Perguntas interessantes
Química,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Administração,
1 ano atrás